δ26Mg, δ44Ca and 87Sr/86Sr isotope ratios constrain Mg and Ca input–output mass balances in a heavily acidified headwater catchment - Martin Novak; Frantisek Veselovsky; Jakub Hruška; Chris Holmden; Alexandre V. Andronikov; Yulia V. Erban Kochergina; Vaclav Kachlik; Marketa Stepanova; Ondrej Pour; Ondrej Sebek; Eva Prechova; Arnost Komarek; et al. (Environmental Sciences Europe)
Abstract A Central European catchment underlain by base-poor orthogneiss was studied using mass budgets and Mg–Ca–Sr isotope systematics. For 50 years, the catchment received large amounts of partly soluble dust from a nearby cluster of coal-burning power plants, while suffering from acid rain and severe spruce die-back. Our objective was to investigate to what extent anthropogenic dust contributes to Mg and Ca in runoff and to identify fractionations affecting Mg and Ca isotope composition of 13 ecosystem pools and fluxes. We hypothesized that if Mg and Ca runoff fluxes were significantly larger than their atmospheric inputs, Mg and Ca isotope ratios in runoff would converge to those of bedrock Mg and Ca. This relationship could be obscured by isotope fractionations. Strontium characterized by negligible isotope fractionations served as a Ca proxy. There was a strong positive correlation between Mg and Ca fluxes via spruce throughfall and catchment runoff. Monitoring of rainfall, canopy throughfall and runoff fluxes revealed a 20-, 15- and 15-fold excess of Mg, Ca and Sr in runoff, respectively, compared to atmospheric deposition fluxes. This sizeable excess per se would indicate predominance of geogenic base cations in runoff. The behavior of Mg and Ca isotopes was de-coupled. Petrographic study indicated that 92% of bedrock Mg was bound to easily dissolving biotite, 97% Ca was present in plagioclase, and nearly all Sr was in orthoclase. While Mg isotope ratios in bedrock and runoff were indistinguishable, corroborating predominantly geogenic Mg in runoff, Ca and Sr isotope ratios in bedrock and runoff were significantly different, consistent with a non-negligible contribution of atmospheric Ca and Sr to runoff. Previous study of sites underlain by felsic rocks indicated that the δ44Ca value of apatite was often higher than the δ44Ca value of plagioclase. Should weathering of apatite and/or plagioclase preferentially release Ca that is isotopically heavier than bulk rock, the geogenic Ca source at JEZ would converge to the mean δ44Ca value of runoff. Calcium isotope data would then become more consistent with a major role of geogenic Ca in JEZ runoff indicated by mass balance data.